Community mothers' programme: extension to the travelling community in Ireland. Issue 3 (June 1997) - Fitzpatrick, P; Molloy, B; Johnson, Z
Abstract : STUDY OBJECTIVE: To see whether the community mothers' programme, using lay volunteer mothers to deliver a childhood development programme, could be extended successfully to the travelling community in Ireland. DESIGN: This was a prospective study of the travelling community; comparisons were made with results of a previous randomised trial of settled mothers. SETTING: A regional health authority in Ireland. PARTICIPANTS: These comprised 39 traveller and 127 settled intervention mother/ infant pairs (randomised controlled trial (RCT) intervention); settled community mothers; 105 settled control pairs (RCT control). All mothers received standard support; traveller and RCT intervention groups also received the services of a community mother. MAIN RESULTS: The travellers' sociodemographic profile differed significantly from the other groups. At the end of the study, traveller and intervention children were exposed to more cognitive games and nursery rhymes. There were significant differences in the proportions who received all three shots of their primary immunisation schedule before 12 months of age and who received "three in one" vaccination, with traveller children doing least well. The diet of traveller children surpassed that of RCT controls in all food groups except fruit; they were less likely to begin cows' milk before 26 weeks of age. Traveller mothers' diet was superior to that of RCT control and similar to RCT intervention mothers. Traveller and RCT intervention mothers were less likely to feel tired, feel miserable, and want to stay indoors than RCT control mothers. CONCLUSIONS: The results of the community mothers' programme in the travelling community are encouraging; poor immunisation uptake remains a challenge.